2023
DOI: 10.1002/sd.2616
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental policies on the profitability of greenhouse agriculture in southeastern Spain

Abstract: Sustainable development has become an essential criterion for structural policies of the European Union, and these policies have extended its environmental dimensions. The EU has decided that circular economy will be framed within the principles of sustainable development. Thus, the changes brought forth will affect activities like agriculture, where environmental policy can undermine the stability of agricultural systems by reducing their profitability. The objective of this study was to evaluate how the impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…To this end, it is necessary to have territorial information on the economic, social, and environmental sustainability of the production system to support the implementation of those strategies with objective data. Previous research has indicated that it is necessary to expand the information in the field of study and adapt it to the needs of each production system (Castillo-Díaz et al, 2022;Castillo-Díaz, Batlles-delafuente, et al, 2023;Cirone et al, 2023;Streimikis & Baležentis, 2020).…”
Section: Sustainability Commitmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, it is necessary to have territorial information on the economic, social, and environmental sustainability of the production system to support the implementation of those strategies with objective data. Previous research has indicated that it is necessary to expand the information in the field of study and adapt it to the needs of each production system (Castillo-Díaz et al, 2022;Castillo-Díaz, Batlles-delafuente, et al, 2023;Cirone et al, 2023;Streimikis & Baležentis, 2020).…”
Section: Sustainability Commitmentsmentioning
confidence: 99%
“…Therefore, it is necessary to identify the specific issues that affect the sustainability of each food production system to establish appropriate management measures and limit negative externalities. For this reason, it is crucial to make the information needed to make a decision available, which is not always the case (Castillo-Díaz, Batlles-delafuente, et al, 2023;.…”
mentioning
confidence: 99%
“…In recent years, there has been an increase in the cost of inputs and means of production in the protected horticultural system of Almeria, which has accelerated recently due to inflation in the Eurozone. Farmers in this system can see how their economic margins are reduced yearly due to the continued stability of the price at origin of fruit and vegetable products [42,131].…”
Section: Cost Analysismentioning
confidence: 99%
“…In recent years, there has been an increase in the cost of inputs and means of production in the protected horticultural system of Almeria, which has accelerated recently due to inflation in the Eurozone. Farmers in this system can see how their economic margins are reduced yearly due to the continued stability of the price at origin of fruit and vegetable products [42,131]. The production system that performs self-management of agricultural biomass through the biodisinfection technique shows a decrease in total production costs ranging from 3.7% to 6.1% (Figure 4).…”
Section: Cost Analysismentioning
confidence: 99%
See 1 more Smart Citation